2021
DOI: 10.21037/atm-20-7442
|View full text |Cite
|
Sign up to set email alerts
|

Regional ventilation distribution in healthy lungs: can reference values be established for electrical impedance tomography parameters?

Abstract: Background: Although electrical impedance tomography (EIT) is widely used for monitoring regional ventilation distribution, reference values have yet to be established for clinical use. The present study aimed to evaluate the feasibility of creating reference values for standard EIT parameters for potential clinical application.Methods: A total of 75 participants with healthy lungs were included in this prospective study (male:female, 48:27; age, 34±14 years; height, 172±7 cm; weight, 73±12 kg). The subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
(42 reference statements)
0
12
1
Order By: Relevance
“…We suspect that, during spontaneous breathing, the inspiration time is too short to have a stable RVD value. A recent study has shown that the coefficient of variation for RVD in healthy subjects was high (30), which might be the reason why no significant difference could be found in the present study.…”
Section: Discussioncontrasting
confidence: 78%
“…We suspect that, during spontaneous breathing, the inspiration time is too short to have a stable RVD value. A recent study has shown that the coefficient of variation for RVD in healthy subjects was high (30), which might be the reason why no significant difference could be found in the present study.…”
Section: Discussioncontrasting
confidence: 78%
“…Changes in GI at higher PEEP levels are very small. Yang et al found that GI varies ~ 4% in healthy, spontaneously breathing volunteers [ 31 ]. Taken this into account, PEEP is still higher but considerable lower in ARDS patients in our population (12.6 cmH 2 O versus 17.1 cmH 2 O).…”
Section: Discussionmentioning
confidence: 99%
“…Smaller indexes mean more homogeneous ventilation (45). GI was validated retrospectively in ARDS patients (46, 47), prospectively in healthy lungs (48), and recently used as a “tiebreaker” for determining the optimal PEEP when the ODCL is equal among different PEEPs (35).…”
Section: Clinical Applications Of Electrical Impedance Tomography − P...mentioning
confidence: 99%
“…Smaller indexes mean more homogeneous ventilation (45). GI was validated retrospectively in ARDS patients (46,47), prospectively in healthy lungs (48), and recently used as a "tiebreaker" for determining the optimal PEEP when the ODCL is equal among different PEEPs (35). 2) Center of Ventilation (CoV): CoV is a geometric reference within the EIT matrix that represents the distribution of ventilation in the vertical and horizontal axes (49).…”
Section: Indexes Of Heterogeneous Ventilationmentioning
confidence: 99%